Bases of the equivariant cohomologies of regular semisimple Hessenberg varieties - Cho, Soojin; Hong, Jaehyun; Lee, Eunjeong (Advances in Mathematics, 2023)
We consider bases for the cohomology space of regular semisimple Hessenberg varieties, consisting of the classes that naturally arise from the Białynicki-Birula decomposition of the Hessenberg varieties. We give an explicit combinatorial description of the support of each class, which enables us to compute the symmetric group actions on the classes in our bases. We then successfully apply the results to the permutohedral varieties to explicitly write down each class and to construct permutation submodules that constitute summands of a decomposition of cohomology space of each degree. This resolves the problem posed by Stembridge on the geometric construction of permutation module decomposition and also the conjecture posed by Chow on the construction of bases for the equivariant cohomology spaces of permutohedral varieties.
Keywords: Equivariant cohomologies; Hessenberg varieties; Permutohedral varieties; Representations of symmetric groups